Modeling vadose zone wells and infiltration basins to compare recharge efficiency in unconfined aquifers - Patton, Erik Mark (Kansas State University, 2017)
In specific lithologic and hydrogeological settings, Managed Aquifer Recharge (MAR) projects using vadose zone wells have the potential to outperform infiltration basins in terms of volume of water recharged. Numerical modeling can assist in determining which recharge method is most efficient in infiltrating water to unconfined alluvial aquifers of differing unsaturated zone lithologic complexities. The Sagamore Lens Aquifer (SLA) in Cape Cod, Massachusetts is an example of an aquifer with minimal lithologic complexity while the Hueco Bolson Aquifer (HBA) near El Paso, Texas has greater lithologic complexity. This research combines two U.S. Geological Survey numerical models to simulate recharge from infiltration basins and vadose wells at these two locations. VS2DTI, a vadose zone model, and MODFLOW-2005, a saturated zone model, were run sequentially at both sites and with both vadose well and infiltration basin recharge methods simulated. Results were compared to determine the relative effectiveness of each method at each location and to determine the effects of vadose zone complexity on recharge. At the HBA location, soil samples were tested for conductivity and grain size distribution and a microgravity survey was begun to constrain the models. The infiltration basin structure proved to be more efficient, infiltrating more water volume at both locations. Lithologic complexity formed perched conditions in the HBA model, significantly affecting infiltration rates from both infiltration methods at that location. Methods and conclusion from this study can assist in the modeling and design of future MAR projects, especially in locations with thick or lithologically complex vadose zones.
Keywords: Vadose zone; ModelingHydrogeology